2012
DOI: 10.1016/j.npbr.2012.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Severe depression is associated with increased microglial quinolinic acid in subregions of the anterior cingulate gyrus: Evidence for an immune-modulated glutamatergic neurotransmission?

Abstract: Background: Immune dysfunction, including monocytosis and increased blood levels of interleukin-1, interleukin-6 and tumour necrosis factor α has been observed during acute episodes of major depression. These peripheral immune processes may be accompanied by microglial activation in subregions of the anterior cingulate cortex where depression-associated alterations of glutamatergic neurotransmission have been described. Methods: Microglial immunoreactivity of the N-methyl-D-aspartate (NMDA) glutamate receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 46 publications
(66 reference statements)
7
89
0
1
Order By: Relevance
“…IL-1 was shown not only to decrease hippocampal neurogenesis in human hippocampal progenitor cells but also to upregulate the expression of the enzymes, IDO, KMO, and kynureninase and, crucially, treatment with a KMO inhibitor reversed the effects of IL-1 on hippocampal neurogenesis (Zunszain et al, 2012). The reduction in GM volume and the decrease in neuronal density that has been found in some depressed patients post-mortem may be related to higher brain concentrations of microglia-derived QA, as was recently reported in subjects with MDD (Steiner et al, 2008(Steiner et al, , 2011. Conversely, psychiatric medication may increase the synthesis of the potentially neuroprotective compound, KA, and/or decrease the synthesis of 3HK.…”
Section: Discussionmentioning
confidence: 69%
“…IL-1 was shown not only to decrease hippocampal neurogenesis in human hippocampal progenitor cells but also to upregulate the expression of the enzymes, IDO, KMO, and kynureninase and, crucially, treatment with a KMO inhibitor reversed the effects of IL-1 on hippocampal neurogenesis (Zunszain et al, 2012). The reduction in GM volume and the decrease in neuronal density that has been found in some depressed patients post-mortem may be related to higher brain concentrations of microglia-derived QA, as was recently reported in subjects with MDD (Steiner et al, 2008(Steiner et al, , 2011. Conversely, psychiatric medication may increase the synthesis of the potentially neuroprotective compound, KA, and/or decrease the synthesis of 3HK.…”
Section: Discussionmentioning
confidence: 69%
“…For example, relative to healthy controls, MDD patients have increased blood KYN (Bay-Richter et al, 2015;Kim et al, 2012;Sublette et al, 2011), and the density of QUIN-positive microglia was increased in anterior cingulate cortex in MDD patients (Steiner et al, 2011) (for review: (Reus et al, 2015)). …”
Section: Psychosocial Stress-induced Activation Of the Kynurenine Patmentioning
confidence: 99%
“…KYN is further metabolized to, among others, 3-hydroxykynurenine (3-HK), quinolinic acid (QUIN) and kynurenic acid (KYNA), catabolites that can contribute to oxidative stress, excitotoxicity, and neuroprotection (for review: (Chiarugi et al, 2001;Haroon et al, 2012;Schwarcz et al, 2012). There is growing evidence for kynureninepathway hyperfunction in stress-related disorders, particularly for MDD (Bay-Richter et al, 2015;Kim et al, 2012;Reus et al, 2015;Savitz et al, 2015;Steiner et al, 2011;Sublette et al, 2011) (for review: (Maes et al, 2011)). …”
Section: Introductionmentioning
confidence: 99%
“…Although much of the attention of the literature has been focused on immunologic parameters in the peripheral blood, it should be noted that although the literature is not entirely consistent (Clark et al, 2016), increased activation of microglial cells as well as increased expression of inflammatory cytokines and Toll-like receptors have been described in postmortem brain samples of presumably depressed suicide victims (Steiner et al, 2008(Steiner et al, , 2011Pandey et al, 2012Pandey et al, , 2014Torres-Platas et al, 2014). Inconsistencies in the literature have been attributed to diagnostic considerations, use of medications, brain regions sampled, and small sample sizes.…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
“…In addition, inflammatory cytokine-induced activation of IDO can lead to the production of quinolinic acid by microglia that can bind to glutamate (N-methyl-Daspartate (NMDA)) receptors while also stimulating glutamate release from astrocytes (Tavares et al, 2002(Tavares et al, , 2005Schwarcz et al, 2012). Indeed, in studies from postmortem tissue of presumably depressed suicide victims, activated microglia expressing quinolinic acid have been described in the anterior cingulate cortex (Steiner et al, 2011). Interestingly, studies in laboratory animals administered LPS have shown that pretreatment with the glutamate antagonist ketamine can reverse LPS-induced depressive-like behavior while having no effect on LPS-induced inflammation in the brain (Walker et al, 2013).…”
Section: Inflammation Effects On Neurotransmitter Metabolismmentioning
confidence: 99%